Pengaruh Penerapan Disiplin Positif terhadap Keterampilan Sosial Peserta Didik Kelas V di SDN 21 Pekanbaru - Engla Guselviana; Zaka Hadikusuma Ramadan (Departement of Mathematics Education, 2024)
This study aims to determine the effect of the application of positive discipline on the social skills of fifth grade students at SDN 21 Pekanbaru. The type of research used is quantitative research. The sample taken was 93 which were fifth grade students. The instruments used were questionnaires and documentation. Validity and reliability tests were used in testing the instrument. The analysis prerequisite test is carried out in 2 stages, namely normality and homogeneity tests. The hypothesis test used is simple linear regression test. The results of this study are that there is an effect of the application of positive discipline on the social skills of fifth grade students at SDN 21 Pekanbaru, this is evidenced in the results of the simple linear regression hypothesis test with a significance value of 0.000 < 0.05. If the significance value is less than 0.05 then there is a relationship/correlation between Positive Discipline (X) and Social Skills (Y).